A first case of primary amenorrhea with i(X)(qter---q10::---qter), rob(13;14)(q10;q10), inv(9)(p13q33) karyotype - Seema Korgaonkar; Kanjaksha Ghosh; Babu Rao Vundinti (Wolters Kluwer Medknow Publications, 2011)
Primary amenorrhea (PA) refers to the absence of menarche by the age of 16-18 years although secondary sexual characters are developed. PA occurs in 1-3% of women in the reproductive age group. Various factors such as anatomical, genetic and hormonal factors reported to influence PA. We report triple chromosomal abnormalities of rob(13;14)(q10;q10),inv(9)(p13q33), i(Xq)(qter---q10::---qter) in a case of PA and short stature. Though proband has multiple chromosome aberrations, genotypic effect of only i(Xq) is evident as proband has PA and short stature. The rob(13;14) and inv(9), which are paternally derived may have role in later reproductive age. Therefore, chromosomal analysis is essential in such cases for the accurate diagnosis and management of the disease.